Study of Light Trapping Scheme to Improve Performance of Silicon Solar Cells - R. Sircar; J. Trivedi; S. Gupta; B. Tripathi; D.P. Srivastava (Журнал нано- та електронної фізики)
The efficiency of solar cells can be increased by applying multidisciplinary approaches that encompass many branches of physics and engineering. One of the important branches of physics namely optics can be used for designing an scheme of light trapping for solar cells to reduce the reflection from the front surface and increasing the optical path length of light within the solar cell. In this paper, the potential of light trapping scheme has been studied and calculations have been done using PC1D base model with a solar cell having texturing on front and rear surface. A maximum output short-circuit current of 5.88 Amperes is obtained with front facet angle 700 and rear facet angle 600 for an area of 125 mm × 125 mm.